A Novel Hydroxylation Step in the Taxane Biosynthetic Pathway: A New Approach to Paclitaxel Production by Synthetic Biology - Sanchez-Muñoz, Raul; Perez-Mata, Edgar; Almagro, Lorena; Cusido, Rosa M.; Bonfill, Mercedes; Palazon, Javier; Moyano, Elisabeth (Frontiers in Bioengineering and Biotechnology, 2020)
Engineered plant cell lines have the potential to achieve enhanced metabolite production rates, providing a high-yielding source of compounds of interest. Improving the production of taxanes, pharmacologically valuable secondary metabolites of Taxus spp., is hindered by an incomplete knowledge of the taxane biosynthetic pathway. Of the five unknown steps, three are thought to involve cytochrome P450-like hydroxylases. In the current work, after an in-depth in silico characterization of four candidate enzymes proposed in a previous cDNA-AFLP assay, TB506 was selected as a candidate for the hydroxylation of the taxane side chain. A docking assay indicated TB506 is active after the attachment of the side chain based on its affinity to the ligand 3’N-dehydroxydebenzoyltaxol. Finally, the involvement of TB506 in the last hydroxylation step of the paclitaxel biosynthetic pathway was confirmed by functional assays. The identification of this hydroxylase will contribute to the development of alternative sustainable paclitaxel production systems using synthetic biology techniques.